Recent Insights Into the Structure, Function, and Evolution of the RNA-Splicing Endonucleases - Hirata, Akira (Frontiers in Genetics, 2019)
RNA-splicing endonuclease (EndA) cleaves out introns from archaeal and eukaryotic precursor (pre)-tRNA and is essential for tRNA maturation. In archaeal EndA, the molecular mechanisms underlying complex assembly, substrate recognition, and catalysis have been well understood. Recently, certain studies have reported novel findings including the identification of new subunit types in archaeal EndA structures, providing insights into the mechanism underlying broad substrate specificity. Further, metagenomics analyses have enabled the acquisition of numerous DNA sequences of EndAs and intron-containing pre-tRNAs from various species, providing information regarding the co-evolution of substrate specificity of archaeal EndAs and tRNA genetic diversity, and the evolutionary pathway of archaeal and eukaryotic EndAs. Although the complex structure of the heterothermic form of eukaryotic EndAs is unknown, previous reports regarding their functions indicated that mutations in human EndA cause neurological disorders including pontocerebellar hypoplasia and progressive microcephaly, and yeast EndA significantly cleaves mitochondria-localized mRNA encoding cytochrome b mRNA processing 1 (Cpb1) for mRNA maturation. This mini-review summarizes the aforementioned results, discusses their implications, and offers my personal opinion regarding future directions for the analysis of the structure and function of EndAs.